Glycemic control among patients with diabetes and comorbid depression in gulf countries: A systematic review - Saad Mohammad Alsaad; Turki A Binmoammar; Sondus Hassounah; Ali H Mokdad; Salman Rawaf (Wolters Kluwer Medknow Publications, 2021)
Background: People with diabetes suffering from depression are at greater risk of suffering from an episode of diabetic burnout which can have adverse outcomes on their health. Objectives: The primary objective is to review the relationship between depression and glycemic control among patients with diabetes in the Gulf Cooperation Council (GCC) countries. Methods: MEDLINE, EMBASE, PsychINFO, and GLOBAL HEALTH databases were systematically searched without language restriction to identify relevant studies that examined the relationship between glycemic control and depression among patients with diabetes in (GCC) countries. Reference lists and Google Scholar were also searched for additional studies. Research was conducted by two reviewers independently and disagreements were resolved by discussion. Results: Our search revealed nine studies were published between 2004 and 2018 and a total of 2199 subjects with diabetes. Majority of the participants were diagnosed with type 2 diabetes mellitus (DM). Out of the 9 articles included in the synthesis, only five of them have reported a significant association between depression and glycemic control; on the other hand, four articles showed nonsignificant association. The prevalence rates of depression among diabetic patients ranged from 12.5% to 61.8%. Conclusion: Depression was associated with poorly controlled HbA1c. However, this association was not significant across all studies. Considering the high rates of DM in these countries, better quality studies are needed to assess the depression comorbidity and its impact on glycemic control for better cost-effective treatments and to inform practice.